PREPARATION OF ZNO NPS BY HYDROTHERMAL METHOD AND THE EFFECT OF PREPARATION TEMPERATURE ON NANOSTRUCTURE PROPERTIES - ALI E. HASHIM; RANIA H. HUSSEIN; HAMSA M. HAWY; MOHAMMED ABDALJABBAR AHMED (IPHO-Journal of Advance Research in Science And Engineering, 2026)
Zinc oxide nanoparticles were prepared by hydrothermal technique under various conditions. The influence of temperature on structure of zinc oxide nanoparticles was studied by x-ray diffraction (XRD) patterns, which confirm the polycrystalline structure of zinc oxide samples. A well-defined diffraction peak at about 36° (101) was observed and this major peak indicates that the hexagonal Structure (ZnO) of zinc oxide was obtained. The field emission-scanning electron microscopy (FE-SEM) studied the surface covered with nanoparticles ,where have different shapes( nanosheets, star shapes and rod), as well as having uniformly distributed over the entire surface and shows that these particles are with average diameter (80.01) ,(60.56) and (152.18)nm respectively. The uv-vis observed small peaks in range (386)nm, absorbance in this region is due to the formation of zinc oxide nanoparticles and the energy band gap was determined in the range 3.1-3.3 eV. The PL spectra showed The recombination of free excitons in the near-band-edge of ZnO caused the peak of the emission locked at around 400 nm in the UV region. FTIR analyses demonstrated Peaks at 564,563 and 750 cm1 are the typical absorption of Zn-O bonds and higher purity of prepared ZnO nano-materials’.